1980
DOI: 10.1136/jnnp.43.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolactin and cortisol concentrations after grand mal seizures.

Abstract: SUMMARY Serial serum prolactin and cortisol levels were measured in five patients after a grand mal seizure and in four volunteers with simulated seizures. Single levels were measured after a witnessed seizure in 26 patients and in a matched control group. Significant increase in both prolactin and cortisol levels occurred after seizures. The change in cortisol level may reflect a nonspecific stress response, but the increase in prolactin levels could not be accounted for on this basis, and probably indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0
3

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(41 citation statements)
references
References 11 publications
1
37
0
3
Order By: Relevance
“…1 and 5) and, therefore, may be used as a baseline substitute. Our study confirms previous observations (Trimble, 1978;Abbott et al, 1980;Collins et al, 1983;Aminoff et al, 1984;Pritchard et al, 1985) indicating that cortisol and PRL concentrations increase in plasma within 60 rnin following a generalized convulsion. The magnitude of the hormonal response in our patients was similar to that reported by others.…”
Section: Discussionsupporting
confidence: 94%
“…1 and 5) and, therefore, may be used as a baseline substitute. Our study confirms previous observations (Trimble, 1978;Abbott et al, 1980;Collins et al, 1983;Aminoff et al, 1984;Pritchard et al, 1985) indicating that cortisol and PRL concentrations increase in plasma within 60 rnin following a generalized convulsion. The magnitude of the hormonal response in our patients was similar to that reported by others.…”
Section: Discussionsupporting
confidence: 94%
“…The half-life of 123 min for cortisol after the seizure in our pa tients with epileptic seizure is twice as high as that after a bolus injection of cortisol to healthy subjects, which is 66 min [13]. The increase in cortisol was less pronounced than that of prolactin and thyrotropin as has been noted else where [1].…”
Section: Discussionmentioning
confidence: 66%
“…Serum norepinephrine was lower in patients compared to healthy subjects (p<0.05). The simultaneous elevation of serum prolactin, thyrotropin, growth hor mone, and cortisol points to a central stimulation of the hypothalamic-pituitary axis during an epileptic seizure, but not during seizures of psychogenic origin.Following a grand mal or complex partial seizure most patients show a rise in serum prolactin levels [1,2,6,12,13,18,22,25,26,35,36]. Electroconvulsive treatment also eli cits in humans a rise in serum prolactin, adrenocortotropic hormone (ACTH), and thyrotropin [4,20,21,23].…”
mentioning
confidence: 99%
“…Seizure activity can cause an outpouring of prolactin in humans (Trimble, 1978;Abbott et al, 1980). Because previous experiments in which EEGs were recorded showed that seizure activity probably had stopped by the time the litters were born (Hawkins and Mellanby, 1987), such an impairment of prolactin secretion would have had to outlast the seizures by several weeks.…”
Section: Discussionmentioning
confidence: 98%